Duke University PA Graduate and student information, 1971. (1971)
This packet of information assembled in 1971 contains information on the distribution of 41 graduates of the Duke University PA Program, the prior health-related backgrounds of graduates and students, a profile of the Class of 1971 and the didactic class schedule for 1970-71.